Evaluation of exposure scenarios on intentional microbiological contamination in a drinking water distribution network. (1st June 2016) - Schijven, Jack; Forêt, Jean Marie; Chardon, Jurgen; Teunis, Peter; Bouwknegt, Martijn; Tangena, Ben
Abstract: Drinking water distribution networks are vulnerable to accidental or intentional contamination events. The objective of this study was to investigate the effects of seeding duration and concentration, exposure pathway (ingestion via drinking of water and tooth brushing and inhalation by taking a shower) and pathogen infectivity on exposure and infection risk in the case of an intentional pathogenic contamination in a drinking water distribution network. Seeding of a pathogen for 10 min and 120 min, and subsequent spreading through a drinking water distribution network were simulated. For exposure via drinking, actual data on drinking events and volumes were used. Ingestion of a small volume of water by tooth brushing twice a day by every person in the network was assumed. Inhalation of contaminated aerosol droplets took place when taking a shower. Infection risks were estimated for pathogens with low ( r = 0.0001 ) and high ( r = 0.1 ) infectivity. In the served population (48 000 persons) and within 24 h, about 1400 persons were exposed to the pathogen by ingestion of water in the 10-min seeding scenario and about 3400 persons in the 120-min scenario. The numbers of exposed persons via tooth brushing were about the same as via drinking of water. Showering caused (inhalation) exposure in about 450 persons in the 10-min scenario and about 1500 in the 120-min scenario. Regardless of pathogen infectivity, if the seeding concentration is 10 6 pathogens per litre or more, infection risks are close to one. Exposure by taking a shower is of relevance if the pathogen is highly infectious via inhalation. A longer duration of the seeding of a pathogen increases the probability of exposure. Graphical abstract: Highlights: Tooth brushing is as relevant as drinking water for exposure to a pathogen in a distribution network. Exposure when showering is relevant if the pathogen is highly infectious via inhalation. A longer seeding duration of a pathogen increases the exposure probability.